Analysis of Failure Behavior Based on the Ring Shear Test in a Bedding Rock Landslide of the Three Gorges Reservoir - Li, Wei-na; Xu, Guang-li; Yu, Zhang (Frontiers in Earth Science, 2022)
Complex geological environment and climatic conditions lead to frequent geological disasters in the Three Gorges Reservoir area. In particular, due to the impact of reservoir impoundment, a large number of landslides have occurred, resulting in huge economic losses and casualties. In this study, the bedding rock landslide is taken as the research object. First, the DTA-138 geotechnical ring shear apparatus system is used for the ring shear test. Second, a two-dimensional numerical model of Shanshucao landslide was established, and simulation was carried out. The main conclusions are as follows: 1) The shear stress–shear displacement curves of sliding zone soil under different shear rates show typical strain softening characteristics. 2) The shear rate–internal friction angle curve showed a good logarithmic relationship. 3) The fundamental reason for the rapid sliding into the river after the instability of the main sliding zone of the Shanshucao landslide is the negative rate effect of the argillized interlayer sliding zone soil in the main sliding zone.